所在する学校の運営母体による小中学生の睡眠習慣の違い：中都市における公立学校と国立学校との比較 - 笠次, 良爾; 森, 隆彰; 安部, 孝文; 渡邊, 將司; 山津, 幸司; 香村, 恵介; 田中, 千晶; 青木, 拓巳; 辻, 延浩; 大石, 寛; 久米, 大祐; 石井, 好二郎 (発育発達研究, 2022)
This study determined differences in sleep habits of fifth through ninth graders by taking into account the school management level to which the children belonged to. A group of 21 researchers from 15 research institutes administered a questionnaire survey to 21,491 fifth to ninth graders, who were attending 76 schools from all regions of Japan. Among the questionnaire respondents, a total of 6,556 fifth to ninth graders (3,245 boys and 3,311 girls) attending municipal or national schools located in medium-sized cities and with no deficiencies in the questionnaire items were included in the analysis. Basic details (such as sex), information on sleep habits (such as waking time, bedtime, sleeping hours on weekdays and holidays, sleep debt, and daytime sleepiness), screen time, and moderate-to-vigorous physical activity was collected via the questionnaire. Children attending national schools had poorer sleep habits for both school type, and the differences were particularly prominent on weekdays. Furthermore, children attending national schools were more likely to exhibit daytime sleepiness. It was also suggested that children attending municipal schools had delayed sleep phase due to long screen time, while children attending national schools had advanced sleep phase due to short screen time, particularly on holidays. In the future, random sampling and longitudinal studies in schools from cities other than medium-sized are required.